2014
DOI: 10.1111/dar.12147
|View full text |Cite
|
Sign up to set email alerts
|

Recreational drug use and binge drinking: Stimulant but not cannabis intoxication is associated with excessive alcohol consumption

Abstract: Stimulant intoxication, but not cannabis intoxication, is associated with binge drinking among young adults, compounding already high rates of binge drinking among people who use these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 43 publications
3
28
0
1
Order By: Relevance
“…McKetin, Chalmers, and colleagues (2014) found that young adult ecstasy users who consumed stimulants on their last Saturday night out were three times more likely to binge drink compared to ecstasy-using peers who were not using stimulants that night. Additionally, these stimulant-intoxicated young adults reported drinking excessively, consuming a median of 20 standard drinks during their night out (McKetin, Chalmers, et al, 2014). The independent association we have observed between nightclub attendance and hazardous alcohol use is longitudinal in nature, suggesting that regular attendance at these venues may promote long-term changes in behaviour.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…McKetin, Chalmers, and colleagues (2014) found that young adult ecstasy users who consumed stimulants on their last Saturday night out were three times more likely to binge drink compared to ecstasy-using peers who were not using stimulants that night. Additionally, these stimulant-intoxicated young adults reported drinking excessively, consuming a median of 20 standard drinks during their night out (McKetin, Chalmers, et al, 2014). The independent association we have observed between nightclub attendance and hazardous alcohol use is longitudinal in nature, suggesting that regular attendance at these venues may promote long-term changes in behaviour.…”
Section: Discussionmentioning
confidence: 62%
“…Research in Australia has shown that illicit stimulant (i.e., ecstasy, methamphetamine, and cocaine) users appear to drink at excessive levels when combining stimulants and alcohol in NEDs. In an online survey of 1,994 18-to 30-year-old Australians, McKetin, Chalmers and colleagues (2014) found that ecstasy users (i.e., respondents who had used ecstasy within the last 12 months) who had consumed stimulants on their last Saturday night out reported consuming a median of 20 standard drinks (McKetin, Chalmers, et al, 2014). Similarly, a study of 220 young adult illicit stimulant users living in Melbourne reported that these young adults consumed a median of 15 standard drinks during their most recent episode of stimulant use (Jenkinson et al, 2014).…”
Section: Combining Alcohol and Amphetamine-type Stimulants -Hazardousmentioning
confidence: 99%
See 3 more Smart Citations